Weight Control and Risk Factor Reduction in Obese Subjects Treated for 2 Years With Orlistat: A Randomized Controlled Trial - Davidson, Michael H; Hauptman, Jonathan; DiGirolamo, Mario; Foreyt, John P; Halsted, Charles H; Heber, David; Heimburger, Douglas C; Lucas, Charles P; Robbins, David C; Chung, Jain; Heymsfield, Steven B (JAMA : the journal of the American Medical Association, 1999)
CONTEXT Orlistat, a gastrointestinal lipase inhibitor that reduces dietary fat absorption by approximately 30%, may promote weight loss and reduce cardiovascular risk factors. OBJECTIVE To test the hypothesis that orlistat combined with dietary intervention is more effective than placebo plus diet for weight loss and maintenance over 2 years. DESIGN Randomized, double-blind, placebo-controlled study conducted from October 1992 to October 1995. SETTING AND PARTICIPANTS Obese adults (body mass index [weight in kilograms divided by the square of height in meters], 30-43 kg/m2) evaluated at 18 US research centers. INTERVENTION Subjects received placebo plus a controlled-energy diet during a 4-week lead-in. On study day 1, the diet was continued and subjects were randomized to receive placebo 3 times a day or orlistat, 120 mg 3 times a day, for 52 weeks. After 52 weeks, subjects began a weight-maintenance diet, and the placebo group (n=133) continued to receive placebo and orlistat-treated subjects were rerandomized to receive placebo 3 times a day (n=138), orlistat, 60 mg (n=152) or 120 mg (n=153) 3 times a day, for an additional 52 weeks. MAIN OUTCOME MEASURES Body weight change and changes in blood pressure and serum lipid, glucose, and insulin levels. RESULTS A total of 1187 subjects entered the protocol, and 892 were randomly assigned on day 1 to double-blind treatment. For intent-to-treat analysis, 223 placebo-treated subjects and 657 orlistat-treated subjects were evaluated. During the first year orlistat-treated subjects lost more weight (mean±SEM, 8.76±0.37 kg) than placebo-treated subjects (5.81±0.67 kg) (P<.001). Subjects treated with orlistat, 120 mg 3 times a day, during year 1 and year 2 regained less weight during year 2 (3.2±0.45 kg; 35.2% regain) than those who received orlistat, 60 mg (4.26±0.57 kg; 51.3% regain), or placebo (5.63±0.42 kg; 63.4% regain) in year 2 (P<.001). Treatment with orlistat, 120 mg 3 times a day, was associated with improvements in fasting low-density lipoprotein cholesterol and insulin levels. CONCLUSIONS Two-year treatment with orlistat plus diet significantly promotes weight loss, lessens weight regain, and improves some obesity-related disease risk factors.